Toxic effects of silver nanoparticles in mammals – does a risk of neurotoxicity exist? - Skalska, Joanna; Strużyńska, Lidia (Folia Neuropathologica, 2015)
Over the last decade, silver nanoparticles have become an important class of nanomaterials utilized in the development of new nanotechnologies. Despite the fact that nanosilver is used in many commercial applications, our knowledge about its associated risks is incomplete. Although a number of studies have been undertaken to better understand the impact of silver nanoparticles on the environment, aquatic organisms and cell lines, little is known about their side effects in mammalian organisms. This review summarizes relevant data and the current state of knowledge regarding toxicity of silver nanoparticles in mammals, as well as the accumulated evidence for potent neurotoxic effects. The influence of nanosilver on the central nervous system is significant because of evidence indicating that it accumulates in mammalian brain tissue